Sustaining power resources through energy optimization and engineering - Vasant, P. (IGI Global, 2016)
As the world continues to evolve technologically, people depend more heavily on energy-dependent systems to fulfill their daily needs. However, as these needs grow, it is important to develop sustainable systems that are reliable, as well as environmentally sound. Sustaining Power Resources through Energy Optimization and Engineering highlights the sustainable development and efficient operation of energy systems being provided to consumers. Featuring emergent research and trends within the area of power optimization and engineering, this book is a crucial reference source for engineers, researchers, sustainability experts, and professionals interested in the improvement and usage of infrastructural energy systems. Â© 2016 by IGI Global. All rights reserved.